2012
DOI: 10.1212/wnl.0b013e3182553c5b
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple sclerosis with restless legs syndrome and other sleep disorders in women

Abstract: Women with MS had a significantly higher prevalence of RLS and daytime sleepiness and an increased risk of developing RLS in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 38 publications
3
40
0
1
Order By: Relevance
“…In addition, Moreira et al (2008) found that RLS is significantly associated with sleep quality, sleep disturbances, and excessive daytime sleepiness (P = 0.02) (16). Moreover, Li et al (2012) reported that the prevalence of RLS and daytime sleepiness is significantly higher among women who suffer from MS and the risk of developing RLS in the future are higher in this group, as well (17). Therefore, due to the high prevalence of RLS and its' worsening effect on sleep quality, the assessment of RLS should be of great consideration in patients with MS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Moreira et al (2008) found that RLS is significantly associated with sleep quality, sleep disturbances, and excessive daytime sleepiness (P = 0.02) (16). Moreover, Li et al (2012) reported that the prevalence of RLS and daytime sleepiness is significantly higher among women who suffer from MS and the risk of developing RLS in the future are higher in this group, as well (17). Therefore, due to the high prevalence of RLS and its' worsening effect on sleep quality, the assessment of RLS should be of great consideration in patients with MS.…”
Section: Discussionmentioning
confidence: 94%
“…Li et al (2012) also studied the association between RLS, other sleep disorders, and MS in a group of women. They reported that the prevalence of daytime sleepiness and RLS was significantly higher among women with MS (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in CIDP, which is an inflammatory immune-mediated neuropathy, the longest lower limbs nerves may be more frequently affected by the inflammatory process. Supporting this hypothesis, the prevalence of RLS is increased in inflammatory disorders of central nervous system, such as multiple sclerosis, 25,26 of which CIDP can be considered the peripheral counterpart, with respect to clinical (relapsing or progressive disease course), pathological (focal demyelination and concomitant axon damage), and pathogenic features.…”
Section: 24mentioning
confidence: 95%
“…RLS symptoms appear usually after the onset of MS (18)(19)(20)23,26,27). There is no relationship between MS subtypes and the presence of RLS (18,20,(22)(23)(24)(25)31).…”
mentioning
confidence: 99%